Aberrant O-glycosylation modulates aggressiveness in neuroblastoma - Cuello, Héctor Adrián (2018)
Neuroblastoma (NB) is the most common pediatric malignancy diagnosed before the first birthday in which MYCN oncogene amplification is associated with poor prognosis. Although aberrant glycosylation is an important actor in cell biology, little is known about its role in pediatric cancers such as NB. In this work we characterized the glycophenotype and the enzyme expression involved in glycans biosynthesis in five established human NB cell lines and in patient-derived primary tumors with different MYCN status. Our results show a high expression of Lewis glycan family both in MYCN-amplified cell lines and patient samples. Additionally, we report that MYCN-amplified cells overexpressed Core 2-initiating glycosyltransferase C2GNT1 in association with specific ST3Gals and FUTs, and showed increased binding to E- and Pselectins. Silencing of C2GNT1 expression in NB cells diminished expression of Lewis glycans, decreased the E- and P-selectin binding, and reduced cell adhesion, migration and proliferation in vitro. Treatment of MYCN-non-amplified cells with Trichostatin A (TSA), an histone deacetylase inhibitor, increased the expression of Lewis glycans and the enzymes involved in their biosynthesis. Our results demonstrate that MYCNamplified NB cells overexpress Lewis family glycans, which belong to the Core 2 O-glycans group. Their expression plays a key role in the malignant behaviour of the NB cells and it is modulated by epigenetic mechanisms.